Eight Bureaucratic Reform Dimensions for Regional Public Service Performance: Delapan Dimensi Reformasi Birokrasi untuk Kinerja Pelayanan Publik Daerah - Anggi Yudistia Wulandari (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Good governance requires efficient, transparent, accountable, and participatory administration capable of delivering citizen-oriented services. Specific Background: Although Indonesia has recorded progress in national reform indicators and electronic government development, local authorities remain the most frequently reported institutions in maladministration complaints, reflecting persistent disparities in service quality. Knowledge Gap: Previous studies largely examined individual jurisdictions and did not systematically integrate reform mechanisms with the enabling and inhibiting conditions shaping implementation across local government contexts. Aims: This study analyzes how bureaucratic reform supports service delivery and identifies the factors determining its implementation in Indonesian local governments. Results: Qualitative library research was conducted using legislation, official government reports, academic literature, and content analysis grounded in New Public Management and good governance. The analysis identifies eight interconnected mechanisms: institutional restructuring, merit-based personnel management, performance accountability, digital transformation, service standardization, innovation, integrated oversight, and citizen satisfaction orientation. Transformational leadership, apparatus competence and integrity, cross-sector coordination, public participation, and regulatory consistency facilitate implementation. Conversely, patrimonial administrative culture, resistance to change, fiscal limitations, and inadequate digital infrastructure constrain sustainable implementation, particularly in resource-limited and remote areas. Novelty: The study develops an integrated, context-sensitive framework connecting structural reform mechanisms with their enabling and inhibiting conditions rather than examining isolated regional cases. Implications: Local authorities should reinforce leadership commitment, merit-based staffing, collaborative coordination, citizen feedback, and adaptive digital strategies, while central government should provide affirmative fiscal support and infrastructure development for disadvantaged regions. Highlights: Institutional restructuring, merit systems, accountability, digitalization, standardization, innovation, oversight, and citizen satisfaction form an integrated framework. Transformational leadership, competent personnel, interagency coordination, citizen participation, and regulatory consistency enable implementation. Patrimonial culture, employee resistance, fiscal limitations, and inadequate technology infrastructure obstruct sustainable delivery. Keywords: Intellectual Capital, Risk Management, Financial Performance, Competitive Advantage.